Nuclear pore and nucleocytoplasmic transport impairment in oxidative stress-induced neurodegeneration: relevance to molecular mechanisms in Pathogenesis of Parkinson’s and other related neurodegenerative diseases - Zainab Riaz; Gabriel S. Richardson; Huajun Jin; Gary Zenitsky; Vellareddy Anantharam; Arthi Kanthasamy; Anumantha G. Kanthasamy (Molecular Neurodegeneration)
Abstract Nuclear pore complexes (NPCs) are embedded in the nuclear envelope and facilitate the exchange of macromolecules between the nucleus and cytoplasm in eukaryotic cells. The dysfunction of the NPC and nuclear transport plays a significant role in aging and the pathogenesis of various neurodegenerative diseases. Common features among these neurodegenerative diseases, including Parkinson’s disease (PD), encompass mitochondrial dysfunction, oxidative stress and the accumulation of insoluble protein aggregates in specific brain regions. The susceptibility of dopaminergic neurons to mitochondrial stress underscores the pivotal role of mitochondria in PD progression. Disruptions in mitochondrial-nuclear communication are exacerbated by aging and α-synuclein-induced oxidative stress in PD. The precise mechanisms underlying mitochondrial impairment-induced neurodegeneration in PD are still unclear. Evidence suggests that perturbations in dopaminergic neuronal nuclei are linked to PD-related neurodegeneration. These perturbations involve structural damage to the nuclear envelope and mislocalization of pivotal transcription factors, potentially driven by oxidative stress or α-synuclein pathology. The presence of protein aggregates, pathogenic mutations, and ongoing oxidative stress can exacerbate the dysfunction of NPCs, yet this mechanism remains understudied in the context of oxidative stress-induced PD. This review summarizes the link between mitochondrial dysfunction and dopaminergic neurodegeneration and outlines the current evidence for nuclear envelope and nuclear transport abnormalities in PD, particularly in oxidative stress. We highlight the potential role of nuclear pore and nucleocytoplasmic transport dysfunction in PD and stress the importance of systematically investigating NPC components in PD.